2017
DOI: 10.3758/s13421-017-0713-4
|View full text |Cite
|
Sign up to set email alerts
|

Event models and the fan effect

Abstract: The current study explored the persistence of event model organizations and how this influences the experience of interference during retrieval. People in this study memorized lists of sentences about objects in locations, such as "The potted palm is in the hotel." Previous work has shown that such information can either be stored in separate event models, thereby producing retrieval interference, or integrated into common event models, thereby eliminating retrieval interference. Unlike prior studies, the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…This durability recently has been seen in a study using the differential fan effect [82]. The differential fan effect is the finding that when information can be integrated and organized into a common event model, such knowing that the potted palm, the pay phone, and the bulletin board are in the museum, then there are no competing event models, and there is no retrieval interference.…”
Section: Events and Retrieval Interferencementioning
confidence: 87%
See 1 more Smart Citation
“…This durability recently has been seen in a study using the differential fan effect [82]. The differential fan effect is the finding that when information can be integrated and organized into a common event model, such knowing that the potted palm, the pay phone, and the bulletin board are in the museum, then there are no competing event models, and there is no retrieval interference.…”
Section: Events and Retrieval Interferencementioning
confidence: 87%
“…This increase in retrieval time with an increase in the number of associations is called a fan effect . Recent work [82] has shown that the differential fan effect persists over long periods of time, largely unchanged. This can be seen in Figure 4 in which a differential fan effect is present both immediately after learning, as well as two weeks later, with only minor changes.…”
Section: Events and Retrieval Interferencementioning
confidence: 99%
“…Spatial location is another powerful organizer of events in memory. It is much easier to remember the association between multiple objects and a single location than the association between multiple locations and a single object (e.g., Radvansky et al 2017). For example, it is easier to remember that a potted plant, an ATM, and a poster are in a lobby than it is to remember that there is a potted plant in a lobby, a library, and a café.…”
Section: Event Memory Is Structured By the Same Dimensions As Perceptionmentioning
confidence: 99%
“…More specifically, people learned a list of sentences about objects in locations, such as “The potted palm is in the museum.” For each object and location, there were either one or three associations, with the stipulation that one concept would have three and the other would have one. Following prior research of the differential fan effect (e.g., Radvansky et al, 2017; Radvansky & Zacks, 1991), these materials were divided into two conditions. The first was the Single Location condition in which a set of sentences were about multiple objects in a single location, such as:…”
Section: Methodsmentioning
confidence: 99%